3D Printing of n‐Al/Polytetrafluoroethylene‐Based Energy Composites with Excellent Combustion Stability. Issue 5 (26th February 2021) - Zheng, Dawei; Huang, Tianwei; Xu, Bing; Zhou, Xu; Mao, Yaofeng; Zhong, Lin; Gao, Bing; Wang, Dunju
Abstract : The development of 3D printing technology provides a new idea for the application of energy‐containing materials as functional reactive materials, which helps Al–F high‐energy materials to achieve customized performance and structure, so that energy transmit can be targeted. A high fuel‐load ink (up to 90 wt%) based on Al‐polytetrafluoroethylene (PTFE) is designed and fabricated using fluororubber (FR) as a binder. The content of FR is directly related to the mechanical properties of ink, and the customized structure from the uniform and stable deposition can be obtained by adjusting the content of FR (10–20 wt%). Under the display of high‐speed photography, the ink shows a strong stability in combustion performance, which is conducive to realize the performance customization of the ink in the application. To better understand the combustion mechanism, the thermal properties and combustion process are analyzed in brief through thermal analysis and the combustion snapshots. Abstract : The research introduces a method of the application of n‐Al/polytetrafluoroethylene (PTFE) thermite in 3D printing by adding F2311. Based on suitable rheological shear‐thinning properties, the composite sticks with a high loading of 75–90 wt% have a stable combustion process and a combustion rate of 2–12 cm s −1 that unchanged with the diameter.